Marysa Navarro Aranguren - García-Sanz Marcotegui, Ángel (Huarte de San Juan. Geografía e Historia, 2014)
Marysa Navarro (Pamplona, 1934) has lived most of her life away from Spain because her father, Vicente Navarro Ruiz (Carcar, 1887 - Montevideo, 1964), a Republican, had to go into exile when the civil war ended with the triumph of Francoist forces. After spending her childhood in France and most of her adolescence in Uruguay, she settled in the United States where she completed her graduate studies, taught and worked for several decades to strengthen the presence of women in higher education. She is a distinguished scholar of Feminist History, the History of Latin American women, and especially Eva Perón. Her writings have made her a foremost scholar on Evita.
Keywords: Navarra; exile; United States of America; university professor; researcher; feminism; Eva Perón